Frank Staff and his role in South African ballet and musical theatre from 1955 to 1959, including a pre-1955 biography - Rosen, Gary (School of Dance, 2017)
Frank Staff was the first South African choreographer to explore the concept of modem ballet in South Africa. Through the creation of his ballet companies, the South African Ballet and later the Frank Staff Ballet, he pursued unusual subject-matter not seen previously on a South African ballet stage. This thesis explores his legacy to South African dance and is divided into ten chapters with a separate introduction and conclusion. The aim, from the outset, has been to trace Frank Staff's career with particular reference to his choreographic contribution to ballet and musical theatre in South Africa. Appraised throughout in terms of critical opinion and dancers' commentaries, the study is chronologically based with emphasis on individual works created by Staff. There is an overview of Staff's early career, the rationale being to trace the earlier part of his career (from 1933 to 1952) in order to provide a basis from which Staff's most creative phase, i.e. that of the 1950's, might be explored. Staff's subsequent return to South Africa and possible reasons for choosing Johannesburg as his domicile are alluded to, as well as his vision for a new Johannesburg ballet company, the creation of the Frank Staff Ballet School and the South African Ballet Company. The South African Ballet's first regional tour to Benoni followed by a short tour to Kimberley and Vereeniging before returning to Pretoria for further performances is detailed and an examination of the South African Ballet's second Johannesburg season in November 1955 is made. An investigation into Staff's choreographic contribution to Leslie French's 1956 Johannesburg production of The Tempest as well as Staff's early involvement with Brian Brooke's musical theatre encapsulates his important contribution to South African musical theatre, which was a major interest throughout his life. 1957 was the most important and prolific period for Staff and his latest choreographic achievements demonstrates a broadening of his creative powers and a reaching out for previously unused influences in terms of dance and subject matter. The thesis' conclusion includes some of the possible frustrations Staff might have encountered as a choreographer working in South Africa during the 1960's and alludes to his Afro-centric works before his illness and untimely death in 1971.